The Influence of Behavioral Counseling Theory with the Technique of Modeling Setting Lesson Study on Self Endurance Class X Students Accommodation in Hospitality 5 Public High School 2 Singaraja - I Kadek Bagus Raka Novta Adi Putra (Department of Guidance and Counseling, FIP, Undiksha, 2018)
This study aims to determine the effect of Behavioral Counseling Theory with the Modeling Setting Lesson Study Technique on Self Endurance. This type of research is Quasi Experiment, with the design of Non Equvalent Pree Postest Only Control Group Design, the sample of this study was taken by using random sampling techniques. The subjects of this study were 35 students in class X Hospitality Accommodation 5 at Singaraja State Vocational High School 2. The process of retrieving data in this study uses the method of observation, interviews, diaries and the Self Endurance questionnaire on the linkert scale pattern. Data were analyzed descriptively and statistical analysis using the t-test formula. Based on the value of the t test above, it is obtained thit of 19.34 with ttab of 1.66 at the significance of 0.05. So that it can be concluded H1 is accepted. So the results of the study show that Behavioral Counseling with the Modeling Technique through Lesson Study has an effect on Self Endurance students